2018
DOI: 10.1029/2017jc013731
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Dissipation Rate of Turbulent Kinetic Energy in Strongly Stratified, Low‐Energy Environments: A Case Study From the Arctic Ocean

Abstract: We compare estimates of the turbulent dissipation rate, ε, obtained independently from coincident measurements of shear and temperature microstructure in the southeastern Beaufort Sea, a strongly stratified, low‐energy environment. The measurements were collected over 10 days in 2015 by an ocean glider equipped with microstructure instrumentation; they yield 28,575 shear‐derived and 21,577 temperature‐derived ε estimates. We find agreement within a factor of 2 from the two types of estimates when ε exceeds 3 ×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(66 citation statements)
references
References 56 publications
4
62
0
Order By: Relevance
“…In a similar series of experiments in the same tank, McFarlane et al (2015) found that the tank-averaged turbulent kinetic energy dissipation rate was ∼ 3.4 × 10 −2 m 2 s −3 at a propeller speed of 325 rpm, and this fell within the range of dissipation rates estimated for rivers in Alberta. Dissipation rates in the ocean range from ∼ 10 −2 to 10 −9 m 2 s −3 (Banner and Morrison, 2018;Wang and Liao, 2016), with a reported lower range in the polar regions ranging from ∼ 10 −3 to 10 −10 m 2 s −3 (Chanona et al, 2018;Scheifele et al, 2018). Therefore, the dissipation rate generated in these experiments falls within the upper limits of values observed in the ocean.…”
Section: Experimental Set-up and Methodssupporting
confidence: 64%
See 2 more Smart Citations
“…In a similar series of experiments in the same tank, McFarlane et al (2015) found that the tank-averaged turbulent kinetic energy dissipation rate was ∼ 3.4 × 10 −2 m 2 s −3 at a propeller speed of 325 rpm, and this fell within the range of dissipation rates estimated for rivers in Alberta. Dissipation rates in the ocean range from ∼ 10 −2 to 10 −9 m 2 s −3 (Banner and Morrison, 2018;Wang and Liao, 2016), with a reported lower range in the polar regions ranging from ∼ 10 −3 to 10 −10 m 2 s −3 (Chanona et al, 2018;Scheifele et al, 2018). Therefore, the dissipation rate generated in these experiments falls within the upper limits of values observed in the ocean.…”
Section: Experimental Set-up and Methodssupporting
confidence: 64%
“…2. This method yields values of the freezing point that are within 0.01 • C or better (Mair et al, 1941;She et al, 2016). The freezing point measurements made during each repeated experiment at a given salinity were averaged and the mean freezing points (± standard deviation) for salinities of 15 ‰, 25 ‰ and 35 ‰ C. C. Schneck et al: Properties of frazil and flocs in different salinities were −0.89 ± 0.02, −1.48 ± 0.02 and −2.09 ± 0.02 • C, respectively.…”
Section: Freezing Point Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parameterizations of this kind, relying on models of internal wave breaking, are most useful away from boundaries, in scenarios of perennial stratification where year-round background fluxes dominate (Randelhoff and Guthrie, 2016), and less so to characterize near-surface mixing. Other promising avenues are approaches based on turbulence structure functions (Wiles et al, 2006), high-frequency Acoustic Doppler Current Profiler measurements, or microstructure sensors deployed on moorings and gliders (Scheifele et al, 2018).…”
Section: Upscaling Primary Production Measurementsmentioning
confidence: 99%
“…8 ai. A study in 2018 [9] suggest that a lower limit for reliable values derived from temperature is no smaller than 2 × 10 −12 W kg −1 (in weakly turbulent envirnoments), nearly three orders greater than the second peak seen in Fig. 8 aii.…”
Section: Data Spread and Lower Detections Limitsmentioning
confidence: 82%